2016
DOI: 10.1038/nrrheum.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

DNA-damaging autoantibodies and cancer: the lupus butterfly theory

Abstract: Autoantibodies reactive against host DNA are detectable in the circulation of most people with systemic lupus erythematosus (SLE). The long-held view that antibodies cannot penetrate live cells has been disproved. A subset of lupus autoantibodies penetrate cells, translocate to nuclei, and inhibit DNA repair or directly damages DNA. The result of these effects depends on the microenvironment and genetic traits of the cell. Some DNA-damaging antibodies alone have little impact on normal cells, but in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 67 publications
2
69
0
Order By: Relevance
“…RA affects all populations, although it is much more prevalent in some groups (e.g., 5-6% in some Native American groups) and much less prevalent in others (e.g., black persons from the Caribbean region) [193]. SLE can be defined as a chronic inflammatory and autoimmune disease that can affect multiple organ systems, including skin, joints, kidneys, and the brain, among others [194]. SLE is characterized by a deposition of immune complexes, which are formed in large amounts as antinuclear antibodies bind to the abundant nuclear material in blood and tissues, along with disturbances in both innate and adaptive immunity and T-cell signaling.…”
Section: Secoiridoids Olive Tree In Autoimmune Diseasesmentioning
confidence: 99%
“…RA affects all populations, although it is much more prevalent in some groups (e.g., 5-6% in some Native American groups) and much less prevalent in others (e.g., black persons from the Caribbean region) [193]. SLE can be defined as a chronic inflammatory and autoimmune disease that can affect multiple organ systems, including skin, joints, kidneys, and the brain, among others [194]. SLE is characterized by a deposition of immune complexes, which are formed in large amounts as antinuclear antibodies bind to the abundant nuclear material in blood and tissues, along with disturbances in both innate and adaptive immunity and T-cell signaling.…”
Section: Secoiridoids Olive Tree In Autoimmune Diseasesmentioning
confidence: 99%
“…One study reported that SLE patients have a more condensed chromatin structure that leads to downregulation of genes that function in NER and HDR and defective DNA repair [34]. Recent work has also provided evidence for the existence of lupus autoantibodies that recognize DNA repair proteins and that are able to enter into the nucleus and inhibit DNA repair (for a review see [35]).…”
Section: Genetics Of Dna Repair and Lupusmentioning
confidence: 99%
“…The anti-dsDNA autoantibody is the critical factor in the pathogenesis of SLE [15]. The level of anti-dsDNA antibodies in serum and anti-dsDNA antibodies deposition in the glomeruli absolutely correlate with lupus nephritis progress in SLE patients [16].…”
Section: Resultsmentioning
confidence: 99%